2008
DOI: 10.1021/ma8016585
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Amorphous and Semicrystalline 1,4-trans-Poly(isoprene) by Dielectric Spectroscopy

Abstract: We have studied the dynamics of amorphous 1,4-trans-poly(isoprene) (trans-PI) with different molecular weights using broadband dielectric spectroscopy over a wide range of temperature ∼T g -70 K to T g + 130 K, and frequencies (10 -1 to 10 6 Hz). Avoiding crystallization by quenching, three dielectric processes (global chain, segmental and local relaxations) were observed in order of decreasing temperature. Both the segmental and local relaxations of the here studied trans-PI, were found to be markedly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 65 publications
4
35
1
Order By: Relevance
“…In Figure 8, the evolution of cooperativity length and fragility index is reported as a function of the content of the crystalline phase (X c ), MAP (X ma ), and residual phases (i.e., the sum of mesophase and RAF [X ra + meso]). We already evoked that the high fragility values obtained for the Th and TCR materials break down the idea of a simple correlation between the degree of crystallinity and the fragility index.As previously discussed, it has been shown that depending on the polymer repeating unit or depending on the crystallization mode, an increase or decrease of the fragility index with an increase of the crystalline phase can be observed 81,85 . In our case also, no clear trend can be extracted from the fragility index variation with degree of crystallinity ( Figure 8b).…”
Section: Investigation Of the Temperature Dependence Of The Structuramentioning
confidence: 80%
“…In Figure 8, the evolution of cooperativity length and fragility index is reported as a function of the content of the crystalline phase (X c ), MAP (X ma ), and residual phases (i.e., the sum of mesophase and RAF [X ra + meso]). We already evoked that the high fragility values obtained for the Th and TCR materials break down the idea of a simple correlation between the degree of crystallinity and the fragility index.As previously discussed, it has been shown that depending on the polymer repeating unit or depending on the crystallization mode, an increase or decrease of the fragility index with an increase of the crystalline phase can be observed 81,85 . In our case also, no clear trend can be extracted from the fragility index variation with degree of crystallinity ( Figure 8b).…”
Section: Investigation Of the Temperature Dependence Of The Structuramentioning
confidence: 80%
“…We chose three crystallization temperatures (T c = 215.15, 219.15 and 221.15 K) whereas for each temperature the crystallization times were t c = 30, 60, 150, 180, 360, and 570 min, respectively. Note that this procedure was successfully applied for crystalline polymers and widely discussed in the literature [12][13][14].…”
Section: Procedures Of Crystallization For Dielectric Measurementsmentioning
confidence: 99%
“…This gum, also called gutta percha or balata, is a kind of rubber with a molecular structure of trans ‐1,4‐polyisoprene that crystallizes easily, which is the reason why the E. ulmoides gum can usually be used as plastics, shape memory materials and rubber with different crosslinking degree like synthetic trans ‐1,4‐polyisoprene . Actually, trans ‐1,4‐polyisoprene has been widely used in many fields, such as machinery, chemicals, electronics, transportation, etc . Trans ‐1,4‐polyisoprene has excellent mechanical properties, including long fatigue life, good abrasion resistance, and low heat buildup .…”
Section: Introductionmentioning
confidence: 99%